2010
DOI: 10.21836/pem20100401
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signaling within growth plates of the radius and tibia after periosteal stripping: an experimental study in lambs

Abstract: SummaryPeriosteal transection and elevation is a standard treatment for angular limb deformities in foals. It is used to correct axis deviations in the limbs at an early age to assure that the foals grow up with straight limbs to improve their chances to reach their full potential as future athletes. Although clinically proven, its mechanisms of action were never elucidated on a more basic scientific level. In this experimental study the molecular response to periosteal stripping was investigated within the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In agreement with these reports, PR decreased density of metaphyseal trabecular bone in both mice models in the current study. A molecular signaling study after PR demonstrated that Indian hedgehog (IHH) was highly expressed in the hypertrophic zone of the growth plate in a lamb model ( von Rechenberg et al, 2010 ). Activated IHH signaling promoted bone formation, but the resulting bone was very fragile and porous due to severe bone resorption ( Mak et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these reports, PR decreased density of metaphyseal trabecular bone in both mice models in the current study. A molecular signaling study after PR demonstrated that Indian hedgehog (IHH) was highly expressed in the hypertrophic zone of the growth plate in a lamb model ( von Rechenberg et al, 2010 ). Activated IHH signaling promoted bone formation, but the resulting bone was very fragile and porous due to severe bone resorption ( Mak et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, work on lambs has shown that periosteal transection and elevation have a direct effect on parthyroid hormone and related peptide, all of which are involved in bone growth (Von Rechenberg et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Acceleration is achieved by hemicircumferential periosteal transection and elevation, whereas retardation requires static compression of hypertrophic chondrocytes at the physis, usually by orthopedic implants such as transphyseal cortex screws or screws and wires. [11][12][13] In 2 small experimental studies, periosteal elevation was not more effective than conservative management. 14,15 Additionally, in a large retrospective cohort study, horses treated with periosteal elevation had poorer outcomes than sibling controls.…”
Section: Introductionmentioning
confidence: 99%
“…The surgical methods described for the correction of angular limb deformities are aimed at either acceleration or retardation of bone growth. Acceleration is achieved by hemicircumferential periosteal transection and elevation, whereas retardation requires static compression of hypertrophic chondrocytes at the physis, usually by orthopedic implants such as transphyseal cortex screws or screws and wires 11–13 . In 2 small experimental studies, periosteal elevation was not more effective than conservative management 14,15 .…”
Section: Introductionmentioning
confidence: 99%